2021
DOI: 10.3389/fimmu.2021.789142
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Fabry Disease Is Related to Glycocalyx Degradation

Abstract: Fabry disease (FD) is an X-linked multisystemic lysosomal storage disease due to a deficiency of α-galactosidase A (GLA/AGAL). Progressive cellular accumulation of the AGAL substrate globotriaosylceramide (Gb3) leads to endothelial dysfunction. Here, we analyzed endothelial function in vivo and in vitro in an AGAL-deficient genetic background to identify the processes underlying this small vessel disease. Arterial stiffness and endothelial function was prospectively measured in five males carrying GLA variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We used the fluorescent eGC markers Ulex europaeus agglutinin-1 (UEA-1) and wheat germ agglutinin (WGA) to quantify changes in the glycocalyx [ 21 , 22 ]. Only a slight but not significant decrease in UEA-1 fluorescence intensity was observed when HUVECs were treated with sFlt-1 (2 µg/mL) for 24 h compared to control cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the fluorescent eGC markers Ulex europaeus agglutinin-1 (UEA-1) and wheat germ agglutinin (WGA) to quantify changes in the glycocalyx [ 21 , 22 ]. Only a slight but not significant decrease in UEA-1 fluorescence intensity was observed when HUVECs were treated with sFlt-1 (2 µg/mL) for 24 h compared to control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the eGC undergoes conformational changes when challenged with multiple biophysical and biochemical factors, including inflammatory factors, high salt (NaCl), and shear and compressive stresses [ 22 , 30 , 34 , 36 ]. A healthy, intact eGC is upright and soft, while a shed eGC is flat and soft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOECs were stained with fluorescein-conjugated Ulex Europaeus (Gorse) Agglutinin I (UEA I, ThermoFisher) (final concentration, 5 μg/mL for 30 min at room temperature) as described previously [ 19 ] and fluorescence was visualized using a Leica DMI4000 microscope. Values were quantified at 459 nm (emission) and 515 nm (excitation) in a plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of monocytes with endothelial cells is also on the basis of eGCX damage. The products of eGCX degradation including heparan sulfate and chondroitin sulfate may enhance the chemotactic migration of monocytes, although glypican 1 mounted on the membrane of endothelial cells is reported to inhibit monocyte adhesion ( 88 90 ). Hence, the destruction of eGCX may be precisely limited to the area where monocytes are recruited most intensively ( 91 , 92 ).…”
Section: Potential Mechanisms Linking Egcx To the Pathogenesis Of Hpsmentioning
confidence: 99%